2003
DOI: 10.1051/gse:2003026
|View full text |Cite
|
Sign up to set email alerts
|

Association between the MHC gene region and variation of serum IgE levels against specific mould allergens in the horse

Abstract: -To investigate whether the equine major histocompatibility complex (MHC) gene region influences the production of mould-specific immunoglobulin E antibodies (IgE), alleles of the equine leukocyte antigen (ELA-A) locus and three microsatellite markers (UM-011, HTG-05 and HMS-42) located on the same chromosome as the equine MHC were determined in 448 Lipizzan horses. Statistical analyses based on composite models, showed significant associations of the ELA-A and UM-011 loci with IgE titres against the recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Wagner et al (2001) detected polymorphisms in the equine Cε gene and suggested that different IgE allotypes may influence its binding to the Fcε receptors in immune system cells. Also in horses, serum IgE levels have been associated with specific allergic reactions (Curik et al, 2003). The AX_463789:g.133T>C polymorphism of the equine Cε gene identified by VychodilovaKrenkova et al (2005) shows a high potential of physiological changes in the immune system of horses since it results in a non-conservative amino acid substitution (serine to proline) in domain I of the heavy chain of IgE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wagner et al (2001) detected polymorphisms in the equine Cε gene and suggested that different IgE allotypes may influence its binding to the Fcε receptors in immune system cells. Also in horses, serum IgE levels have been associated with specific allergic reactions (Curik et al, 2003). The AX_463789:g.133T>C polymorphism of the equine Cε gene identified by VychodilovaKrenkova et al (2005) shows a high potential of physiological changes in the immune system of horses since it results in a non-conservative amino acid substitution (serine to proline) in domain I of the heavy chain of IgE.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of lipopolysaccharide recognition also involves Toll-like receptors (Fujihara et al, 2003), such as that encoded by the TLR4 gene (Toll-like receptor 4). Equine immunoglobulin E (IgE), partially encoded by the Cε gene, resembles the immunoglobulins of other species (Navarro et al, 1995) and its serum levels have been associated with specific allergic reactions (Curik et al, 2003). Vychondilova-Krenkova et al (2005) identified 10 SNPs in four genes related to the immune response in horses, CD14, TLR4, Cε and FcεR1 alpha, and developed genotyping techniques to be used in association studies of gene polymorphisms with phenotypes of interest.…”
mentioning
confidence: 99%
“…In horses, type I hypersensitivity has been investigated, suggesting that this reaction might be involved in immune-mediated diseases such as summer eczema (Larsen et al 1988;Ungar-Waron et al 1990), urticaria, and head shaking (Mansfield et al 1998), as well as RAO (Halliwell et al 1993;Schmallenbach et al 1998;Eder et al 2000;Eder et al 2001;Curik et al 2003;Künzle et al 2007; Morán et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…In general, airway inflammation in RAO-affected horses involves the activation of pathogen specific inflammatory cells, modulation of gene transcription factors and the release of inflammatory mediators (Bureau et al 2000 a,b ). Type I hypersensitivity, which is IgE-mediated , Schmallenbach et al 1998, Eder et al 2000, Eder et al 2001, Curik et al 2003, Künzle et al 2007, Tahon et al 2009, Moran et al 2010, and type III hypersensitivity reactions have been suggested to play a role in airway inflammation in RAO-affected horses (Franchini et al 2000, Lavoie et al 2001.…”
Section: Introductionmentioning
confidence: 99%